Cheerfulness : A Literary and Cultural History - Hampton, Timothy (Book collections on Project MUSE., 2022)
"This book offers the first study of a form of emotion that has inflected both the social life and the literary history of the European/American cultural tradition since the Renaissance. It explores the changing fortunes and shapes of cheerfulness and gaiety in cultural texts ranging from the tragedies of Shakespeare to the music of Louis Armstrong. It recasts our understanding of the relationship between poetry and the emotions, and models a new approach to writing about feeling. Recent years have seen a growing bookshelf of studies in the history of emotion and in what is now called "affect theory." Most of this work deals in either heavy-handed generalizations (the Renaissance as "the age of melancholy") or jargon-filled attempts to grasp the emotional life of our miserable present (books on ugliness, melancholy, cruelty, etc.). Cheerfulness presents a scholarly challenge. It is a modest emotional force, yet, as Emerson says, also a "power." It predates our current misery, emerging as a topic of reflection at the time of the Renaissance, in debates over Biblical interpretation. And it is a central feature of both the emotional life of the West and the artistic legacy of poetry since the end of the Middle Ages. Yet what is cheerfulness? Philologically, it is related to a Middle French word meaning "face;" and in part the history of cheerfulness is the history of a certain understanding of the face. Yet cheerfulness escapes most of the categories that have been invented to discuss emotion. It does not fit into the classical canon of the "passions," even though it is often mentioned in pre-modern medical writing. It emerges and circulates, not within the individual, but between subjects, in the social presentation of the self and in the interplay of groups. Hume calls it a "contagion." It is generally understood to be ephemeral, only visible when in use, difficult to describe abstractly. It touches on the domain of the "affects": yet Spinoza, the great theorist of affect, sets it apart from other phenomena in his discussions of the self. Most important, it is a force that one can control. You cannot "make yourself" melancholy or happy; but you can "make yourself" cheerful. This means that cheer is a force that migrates through the individual subject, shaping her, influencing the quality of the environs, yet somehow also under individual control. It can become a "technique" of selfhood, a force that can be deployed and, as I put it, "used"-by philosophies, discourses, poetic projects. Through a series of 12 interlocking chapters, the book tracks the shifting ways in which major writers and thinkers understand and "use" the idea of cheerfulness in their descriptions of subjectivity, community, and emotion. The discussion ranges from canonical works of literature and philosophy (by Shakespeare, Milton, Montaigne, Dickens, Hume, Austen, Nietzsche) to writing by doctors, theologians, economists, and popular psychologists, from Julian of Norwich to Norman Vincent Peale"--